Pengaruh Analisis Jabatan dan Perencanaan Sumber Daya Manusia terhadap Rekrutmen Karyawan - Irvianti, Laksmi Sito Dwi; Adi, Julius (Bina Nusantara University, 2010)
PD Karunia Jaya is a trading company engaged in supplying spare parts of four-wheeled vehicles. The company originally only deals in one brand, namely Toyota. But, with more and more development, it grew to deal with four brands, including Toyota, Suzuki, Daihatsu, and Isuzu. Due to the increase in the number of brands, the company certainly requires added labor. The purpose of this study is to perform role analysis and human resources planning on employee recruitment at the company. Results obtained can be used as a reference or a guide for companies in developing effective recruitment. The method of analysis used in this study are correlation analysis and linear regression. Data is obtained by spreading the questionnaire to employees. Results achieved in this research is that role analysis is strongly associated with the recruitment at (0.702) and HR planning with recruitment at (0.736). Job analysis and human resource planning is strongly correlated to recruitment at (0.778). Also job analysis has medium influence with recruitment at (0.492) and HR planning with the recruitment at (0.541). Job analysis and human resources planning is associated with the recruitment at (.605). With this results it is expected that role of job analysis and human resource planning can be a major factor to improve the effectiveness of employee recruitment.